A New Target Organ of Leishmania (Viannia) braziliensis Chronic Infection: The Intestine - Santos, Amanda Gubert Alves dos; da Silva, Maria Gabriela Lima; Carneiro, Erick Lincoln; de Lima, Lainy Leiny; Fernandes, Andrea Claudia Bekner Silva; Silveira, Thaís Gomes Verzignassi; Sant’Ana, Debora de Mello Gonçales; Nogueira-Melo, Gessilda de Alcantara (Frontiers in Cellular and Infection Microbiology, 2021)
Leishmania (Viannia) braziliensis is one of the main causes of cutaneous leishmaniasis in the Americas. This species presents genetic polymorphism that can cause destructive lesions in oral, nasal, and oropharyngeal tracts. In a previous study, the parasite caused several histopathological changes to hamster ileums. Our study evaluates immune response components, morphological changes, and effects on neurons in the ileums of hamsters infected by three different strains of L. (V.) braziliensis in two infection periods. For the experiment, we separated hamsters into four groups: a control group and three infected groups. Infected hamsters were euthanized 90- or 120-days post infection. We used three strains of L. (V.) braziliensis: the reference MHOM/BR/1975/M2903 and two strains isolated from patients who had different responses to Glucantime® treatment (MHOM/BR/2003/2314 and MHOM/BR/2000/1655). After laparotomy, ileums were collected for histological processing, biochemical analysis, and evaluation of neurons in the myenteric and submucosal plexuses of the enteric nervous system (ENS). The results demonstrated the increase of blood leukocytes after the infection. Optical microscopy analysis showed histopathological changes with inflammatory infiltrates, edemas, ganglionitis, and Leishmania amastigotes in the ileums of infected hamsters. We observed changes in the organ histoarchitecture of infected hamsters when compared to control groups, such as thicker muscular and submucosa layers, deeper and wider crypts, and taller and broader villi. The number of intraepithelial lymphocytes and TGF-β-immunoreactive cells increased in all infected groups when compared to the control groups. Mast cells increased with longer infection periods. The infection also caused remodeling of intestinal collagen and morphometry of myenteric and submucosal plexus neurons; but this effect was dependent on infection duration. Our results show that L. (V.) braziliensis infection caused time-dependent alterations in hamster ileums. This was demonstrated by the reduction of inflammatory cells and the increase of tissue regeneration factors at 120 days of infection. The infected groups demonstrated different profiles in organ histoarchitecture, migration of immune cells, and morphometry of ENS neurons. These findings suggest that the small intestine (or at least the ileum) is a target organ for L. (V.) braziliensis infection, as the infection caused changes that were dependent on duration and strain.